Reflections and questions on the role of public reading libraries in developing countries - Maris Fernández, Stella (2001)
The new and multiple functions that the public library must currently serve as a result of an increasingly heterogeneous and indefinite public pose a series of dilemmas: are libraries capable of serving all functions, what are the priorities in the face of the evolution that each one of them supports, what is this reality in developing countries such as Argentina with political instability, without economic development and without awareness, at the level of the authorities, of the value and importance of these institutions?